An Overview of Research in the Field of Human Papilloma Virus (HPV) in Iran: a Systematic Review - Nematollahi, Shahrzad; Abdoli, Mitra; Aliakbari, Fereshteh; Sheikh-Milani, Arezoo; Abbasi-Fashami, Mahta; Hosseini, Maryam (Archives of Men's Health, 2020)
Introduction: Human Papilloma Virus (HPV) has many different epidemiological, social and political aspects. The aim of this study was to determine the research priorities according to the necessary aspects of HPV in Iran. Methods: The national and international databases were searched to obtain the published articles regarding HPV in Iran. All Epidemiologic studies were included in this review to assess research priorities. Results: Of 148 studies involving 14,661 participants, the most studies were conducted in Tehran (44.75%) province. Measuring prevalence of HPV (n=63, 42.5%), diagnosis of HPV by molecular techniques (n=52, 35.1%), Knowledge, Attitude and Practice studies (KAP) (n=13, 8.7%), vaccine efficacy (n=8, 5.4%), cost and cost effectiveness analysis (n=4, 2.7%), co-infection of HPV and sexually transmitted diseases (n=5, 3.3%) were the frequent aims of the included studies. Sixty percent (n=57) of the studies were conducted in clinical patients including patients with cervical cancer (n=30, 52.6%), patients with prostate cancer/Benign Prostate Hyperplasia (n=6, 10.5%), and patients with Esophageal carcinoma (n=5, 8.7%). Conclusion: According to our results, the high-risk groups such as female sex workers, injecting drug users and prisoners are in priority for research in the field of HPV. Despite ample epidemiologic studies on prevalence and association of HPV with specific cancers, evidence towards effectiveness and cost-benefits of HPV vaccination is required to prevent the infection and its complicated clinical consequences.